Revisiting the Ambivalent Sexism Inventory’s Adolescent and Brief Versions: Problems, solutions, and considerations - Juarros-Basterretxea, Joel; Ocampo, Nadia Yazmin; Rojas-Solis, José Luis; Rodríguez-Díaz, Francisco Javier; García-Cueto, Eduardo (Anales de Psicología / Annals of Psychology, 2023)
The Ambivalent Sexism Inventory (ASI) has been widely used in applied research and sometimes modified versions have been proposed. The current research aimed to test the factor validity and reliability of the ASI for adolescents (ASI-A) and Brief ASI (B-ASI) versions in the adolescent population. Two analogue samples of Mexican secondary students (Study 1: n1 = 975; Study 2: n2 = 1020) composed the sample. The ASI-A showed that the two-dimension model omitting items 1 to 4 is the most recommendable model and it presents an acceptable fitting to the data (Study 1). The B-ASI bidimensional model showed an appropriate fitting to the data and no modifications were required (Study 2). The ASI-A is a valid measure of ambivalent sexism when some of its items are omitted, but the demonstrated validity of the original items in the adolescent population supports that there was no theoretical or empirical reason for developing a specific version for adolescents of the ASI.